2019
DOI: 10.1108/ijssp-04-2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of cooperation, resilience and resistance: workers’ self-recovery in times of crisis

Abstract: Purpose Worker-recuperated enterprises have appeared in Europe with increasing frequency since 2008, following the Great Recession that hit the western economies. The purpose of this paper is to depict the phenomenon of worker-recuperated enterprises in Italy, focusing on two different types of business recovery, that of workers buyouts and that of recovered social spaces. The paper compares these on the basis of four analytical dimensions: resilience/resistance, relationship with the market, relationship with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Alternatively, when consumers are granted a fine price‐quality ratio (consumer cooperatives), they benefit from a higher quality of life. Understanding the positive externalities produced by cooperatives is evolving and refining as an increasing number of studies on the subject are published (Antonazzo, 2019; Muñoz et al, 2020). Our cases support the reasoning that cooperatives can enhance an economic system's resilience, making it more adaptive and capable of absorbing economic shocks.…”
Section: Contributions Limitations and Future Researchmentioning
confidence: 99%
“…Alternatively, when consumers are granted a fine price‐quality ratio (consumer cooperatives), they benefit from a higher quality of life. Understanding the positive externalities produced by cooperatives is evolving and refining as an increasing number of studies on the subject are published (Antonazzo, 2019; Muñoz et al, 2020). Our cases support the reasoning that cooperatives can enhance an economic system's resilience, making it more adaptive and capable of absorbing economic shocks.…”
Section: Contributions Limitations and Future Researchmentioning
confidence: 99%
“…Over 86% of the BCCs are in Québec, where there is a favourable social economy and co-operative development policy and support (Schwettmann 2014). Similar case studies are reported of WRC enterprises or worker buyouts in Italy and the rising practice of business transfers to or recovery of social spaces for employees in Europe (Antonazzo 2019), and other and conversion models in the USA where Social Economy and Solidarity laws have been adopted (Azzellini 2016;Ji 2020). In Italy the law was enacted to safeguard jobs, facilitating the recovery of companies in crisis through the establishment of workers' cooperatives among redundant employees.…”
Section: Case Studiesmentioning
confidence: 62%
“…The 39 persons were contacted and interviewed. The adoption of a narrative approach in this research is methodologically consistent with an ontological and epistemological position that considers society made of meaningful actions and interpretation as the principal mode of enquiry (Antonazzo, 2019).…”
Section: Methodsmentioning
confidence: 70%